Treatment options of traditional Chinese patent medicines for dyslipidemia in patients with prediabetes: A systematic review and network meta-analysis - Jiang, Li; Wang, Shidong; Zhao, Jinxi; Chien, Chieh; Zhang, Yaofu; Su, Guanxun; Chen, Xiaoyu; Song, Dechao; Chen, Yu; Huang, Weijun; Xiao, Yonghua; Cao, Yandong; et al. (Frontiers in Pharmacology, 2022)
Objective: To compare the clinical efficacy and safety of SIX Traditional Chinese Patent Medicines (TCPM) recommended by guidelines in improving lipids for patients with prediabetes by network meta-analysis. Methods: Randomized controlled trials of 6 TCPM in the treatment of prediabetes were searched systematically in various databases. After extracting effective data, the risk of bias was assessed using Review Manager 5.3 and Cochrane Collaboration Systems Evaluator’s Manual. Network meta-analysis was performed using STATA 15.0 based on the frequency statistical model. The effect size and credibility of the evidence for the intervention were summarized based on a minimal contextualized framework. Results: A total of 27 studies involving 2,227 patients were included. Compared with lifestyle modification (LM), Shenqi + LM [SMD −0.49 (95% CI: −0.85, −0.12)] and Jinqi + LM [SMD −0.44 (95% CI: −0.81, −0.06)] showed statistically significant effect in lowering TG, Shenqi + LM [SMD −0.51 (95%CI: −0.86, −0.17)] and Jinqi + LM [SMD −0.44 (95%CI: −0.80, −0.08)] in lowering TC, Jinlida + LM [SMD −0.31 (95%CI: −0.59, −0.04)] in lowering LDL-C, Shenqi + LM [SMD 0.29 (95%CI: 0.06, 0.51)] and Jinqi + LM [SMD 0.16 (95%CI: 0.01, 0.31)] in increasing HDL-C. Conclusion: For patients with prediabetes, Traditional Chinese patent medicine Jinqi and Shenqi combined with lifestyle modification were associated with a significant reduction in TG and TC, while Shenqi + LM was among the most effective. Jinlida + LM was among the least effective. Systematic Review Registration:https://clinicaltrials.gov/, identifier PROSPERO(CRD42021279332).